EFEKTIFITAS PROGRAM TAX AMNESTY JILID II DAN FAKTOR KEBERHASILAN DAN PERMASALAHAN: PELAJARAN DARI TAX AMNESTY JILID I - Safri Safri (JURNAL MITRA MANAJEMEN, 2021)
ABSTACTThe success of the tax amnesty target for property declaration volume I is not proportional to the number of tax amnesty participants. The number is far below the total number of taxpayers which reached 32 million, and the least number of participants came from MSMEs. With the increase in the taxpayer compliance ratio in reporting the 2020 SPT by 78%, even during the Covid-19 pandemic, of course, a breath of fresh air for the success of the second tax amnesty. This study uses data types with systematic analysis methods, qualitative descriptive analysis is used in data analysis. The purpose of the tax amnesty is to increase state revenues, increase basic data, and assess taxpayer compliance in carrying out their tax obligations, although there are opportunities in the implementation of tax amnesty volume II, there are also problems that need to be studied, lack of socialization of tax amnesty, tax amnesty rates that In contrast, the Tax Amnesty endangers honest taxpayers. The success of the State in tax amnesty is due to the threat that this amnesty is the last amnesty program. Keywords: Tax Amnesty